A Study to Evaluate the Impact of M-teaching on Knowledge, Attitude, and Practice about Digital Health Utilization in Tuberculosis Prevention and Control among Active Tuberculosis Cases and Their Close Contacts in Faridabad, Haryana - Barkha Rani; Anu Gauba; Vivek Jaglan; Sanjay Kumar Mattoo (Indian Journal of Public Health)
Background: The wise use and deployment of digital health (e/m-health) technologies with conventional approaches (in-person directly observed therapy) can play an essential role in improving access to information and providing people-centered tuberculosis (TB) care and support, preventing and controlling TB more effectively globally (by 2030) and in India (by 2025). Objectives: The objectives of this study were to assess the knowledge, attitude, and practice (KAP) level and to evaluate the impact of “mobile-based teaching session” (time taken: 10–12 min) on that KAP level toward digital health technology utilization for TB prevention and control. Materials and Methods: A preexperimental (single group) pre- and posttest design was employed with cluster simple random sampling among 51 active TB cases and their close contacts (age group: 12–78 years) in Faridabad, Haryana, from July to October 2022. Data were collected through telephonic interviews (total time taken: 5–6 min) using a structured questionnaire. The Wilcoxon signed-rank test was computed to compare pre- and posttest rank scores using the SPSS (29.0.0.0) version at the P < 0.05 (two-tailed) significance level. Results: Despite having a positive attitude, the majority showed a lower knowledge and practice level preintervention, whereas after the intervention, their KAP level improved statistically significantly. Conclusions: The study results provide a significant preliminary base for decision-makers and health-care providers to plan and impart digital literacy for TB prevention and control more effectively.